2006
DOI: 10.1103/physrevb.74.125118
|View full text |Cite
|
Sign up to set email alerts
|

Potential superhard osmium dinitride with fluorite and pyrite structure: First-principles calculations

Abstract: We have performed systematic first-principles calculations on di-carbide, -nitride, -oxide andboride of platinum and osmium with the fluorite structure. It is found that only PtN2, OsN2 and OsO2 are mechanically stable. In particular OsN2 has the highest bulk modulus of 360.7 GPa. Both the band structure and density of states show that the new phase of OsN2 is metallic. The high bulk modulus is owing to the strong covalent bonding between Os 5d and N 2p states and the dense packed fluorite structure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(43 citation statements)
references
References 47 publications
4
31
2
Order By: Relevance
“…For P nnm phase, the calculated lattice parameters are in good agreement with the reported experimental and theoretical values [8,9,31,32], and larger deviations from the experimental lattice parameters are found in both a (0.82%) and b (0.58%) directions, respectively, but smaller deviation from the experimental lattice parameters is found in c (0.71%) direction. For F m-3m phase, the calculated lattice parameters are also in good agreement with the reported calculated results [7,12,33,34].…”
Section: Structural Propertiessupporting
confidence: 80%
See 2 more Smart Citations
“…For P nnm phase, the calculated lattice parameters are in good agreement with the reported experimental and theoretical values [8,9,31,32], and larger deviations from the experimental lattice parameters are found in both a (0.82%) and b (0.58%) directions, respectively, but smaller deviation from the experimental lattice parameters is found in c (0.71%) direction. For F m-3m phase, the calculated lattice parameters are also in good agreement with the reported calculated results [7,12,33,34].…”
Section: Structural Propertiessupporting
confidence: 80%
“…The Poisson ratio v provides more information about the characteristics of the bonding forces than any of the other elastic constants. The Poisson ratio v of C2/m is 0.28 (0.28) with GGA (LDA), much larger than diamond (0.08) [7], slightly greater that P 2 1 /c phase (0.26) and P nnm phase (0.24), but smaller than F m-3m phase (0.36).…”
Section: Elastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed the fluorite phase of platinum nitride can be mechanically stable and their calculated bulk modulus is 316 GPa using the local density approximation (LDA) exchange-correlation functional. Later studies [2,[12][13][14] have furthermore suggested that platinum nitride is stable in the pyrite structure with a stoichiometry of PtN 2 . In the pyrite structure nitrogen atoms occupy octahedral interstitial sites of the face-centered cubic (fcc) Pt lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The desire to understand such properties has stimulated a large number of theoretical investigations of structural properties and electronic structure of platinum nitride [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%